2022
DOI: 10.1002/pip.3540
|View full text |Cite
|
Sign up to set email alerts
|

Organic/silicon nanowires hybrid solar cells using isobutyltriethoxysilane incorporated poly(3,4‐ethylenedioxythiophene):poly (styrenesulfonate) as hole transport layer

Abstract: Hybrid heterojunction solar cells (HHSCs) using c‐Si nanowires (SiNWs) as the absorber and poly(3,4‐ethylenedioxythiophene):poly (styrenesulfonate) (PEDOT:PSS) as the hole selective transport layer (HTL) have been drawing more and more attention due to low cost process as well as high power conversion efficiencies (PCE). However, strong hygroscopicity of the PEDOT:PSS film causes serious degradation of the HHSCs. To improve the stability of the HHSCs, a kind of silane impregnating agent, isobutyltriethoxysilan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Based on the average transmittance values of DFPC, transmittance values of 85% or more were classified as "good", values between Long-term stability performance of dopant-free solar cells using different DFPC materials and coating methods under ambient conditions. [28,31,105,146,163,[179][180][181][182][183][184][185][186][187][188][189][190][191][192][193] The results obtained under 85 °C/85% RH conditions are marked with star symbols.…”
Section: Overall Performance Of Dfpc Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the average transmittance values of DFPC, transmittance values of 85% or more were classified as "good", values between Long-term stability performance of dopant-free solar cells using different DFPC materials and coating methods under ambient conditions. [28,31,105,146,163,[179][180][181][182][183][184][185][186][187][188][189][190][191][192][193] The results obtained under 85 °C/85% RH conditions are marked with star symbols.…”
Section: Overall Performance Of Dfpc Materialsmentioning
confidence: 99%
“…Figure 4.Long-term stability performance of dopant-free solar cells using different DFPC materials and coating methods under ambient conditions [28,31,105,146,163,[179][180][181][182][183][184][185][186][187][188][189][190][191][192][193]. The results obtained under 85 °C/85% RH conditions are marked with star symbols.…”
mentioning
confidence: 99%
“…Conductive PEDOT:PSS films exhibit lower mechanical stability due to the hydrophilic nature of PSS. Moisture due to PSS also decreases the cohesion among PEDOT grains resulting in lower conductivity. In order to solve these problems, a lot of research has been carried out by researchers in the last several years by copolymerization, mixing of suitable polymers, ,, inorganic silanes, , and hydrophobic materials, , and protective overcoating. , Organosilicate derivatives are particularly interesting because they can act as a good bridging and compatible material between the inorganic ITO anode surface and the adjacent organic layer with good adhesion property. Recently, several studies reported organo-silicates with good mechanical hardness and hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…[4] For the PEDOT:PSS/Si HHSCs with the structure of "front PEDOT:PSS" in which the PEDOT:PSS layer acts as the optical window and hole transport layer, efficiencies of 16-18% were achieved. [5][6][7] On the other hand, devices with the "back PEDOT:PSS" structure, where PEDOT: PSS hole transport layer was spin coated at backside of the Si substrates to prevent the parasitic absorption of PEDOT:PSS, have achieved the highest efficiencies of 18.8% on n-Si substrates and 20.6% on p-Si substrates. [8,9] However, research on p-Si-based low-temperature solutionprocessed high-efficiency solar cells has not been achieved yet.…”
Section: Introductionmentioning
confidence: 99%